2021
DOI: 10.3390/nu13030720
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Associations between Mothers and Children’s Breakfast Routine—The Feel4Diabetes-Study

Abstract: Positive influences of family members have been associated with a high probability of children’s daily breakfast consumption. Therefore, the aim of this study was to scrutinize the association of breakfast routines between mothers and their children. The baseline data of the Feel4Diabetes-study was obtained in 9760 children (49.05% boys)–mother pairs in six European countries. A parental self-reported questionnaire gauging the frequency of breakfast consumption and of breakfast´ foods and beverages consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Previous studies consistently demonstrate that the home food environment and parental dietary habits are determinants of children's dietary intake [44,45]. Several cross-sectional studies reported a positive association between parental and children's intake of some of MD's beneficial compounds [46,47]. More precisely, recently published studies showed that fathers' fruit and vegetable intake was positively associated with children's intake of these foods [47] as well as that the highest percentage of children who always consumed breakfast were those whose mothers always consumed it [46].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies consistently demonstrate that the home food environment and parental dietary habits are determinants of children's dietary intake [44,45]. Several cross-sectional studies reported a positive association between parental and children's intake of some of MD's beneficial compounds [46,47]. More precisely, recently published studies showed that fathers' fruit and vegetable intake was positively associated with children's intake of these foods [47] as well as that the highest percentage of children who always consumed breakfast were those whose mothers always consumed it [46].…”
Section: Discussionmentioning
confidence: 97%
“…Several cross-sectional studies reported a positive association between parental and children's intake of some of MD's beneficial compounds [46,47]. More precisely, recently published studies showed that fathers' fruit and vegetable intake was positively associated with children's intake of these foods [47] as well as that the highest percentage of children who always consumed breakfast were those whose mothers always consumed it [46]. Additionally, the previous research suggests that maternal consumption of healthy food (e.g., fruit, vegetables, dairy, and cereals,) and unhealthy foods (e.g., fats, snack foods, and oils) is associated with a child's higher intake of the same foods [48].…”
Section: Discussionmentioning
confidence: 99%